Simbolisme Penyembuhan dalam Serat Tetamba II Kajian Semiotik Riffaterre - Bella Nur Putri; Yosi Wulandari (JENTERA: Jurnal Kajian Sastra, 2025)
The aim of this study is to reveal the hidden meanings of the symbols in the text and their role in clarifying traditional healing practices in Java. The method employed is a qualitative approach through literature study, which includes exploring the Serat Tetamba II manuscript, the transformed script, and relevant references related to Javanese healing culture. Data analysis was conducted using Riffaterre’s semiotic theory, which examines shifts in meaning through the mechanisms of displacing, distorting, and creating, as well as the hypogram as a source of hidden meaning that shapes the symbolic structure of the text.The findings indicate that various healing symbols in the manuscript such as colors, animals, sacred objects, medicinal plants, and mantras function not only as technical tools in treatment but also as spiritual elements that strengthen the symbiosis between humans and supernatural forces. These symbols show that healing in Javanese tradition is holistic, integrating physical, mental, and cosmological dimensions. Abstrak Tujuan dari penelitian ini adalah untuk mengungkap arti tersembunyi dari simbol-simbol dalam teks dan peranannya dalam memperjelas praktik pengobatan tradisional yang ada di Jawa. Metode yang diterapkan adalah pendekatan kualitatif dengan studi pustaka, yang mencakup eksplorasi naskah Serat Tetamba II, hasil transformasi aksara, serta referensi literatur yang berhubungan dengan budaya penyembuhan di Jawa. Analisis data dilakukan dengan menerapkan teori semiotik Riffaterre yang meneliti cara-cara penyimpangan makna melalui mekanisme displacing, distorting, dan creating, serta hypogram sebagai sumber makna tersembunyi yang membentuk struktur simbolik dalam teks. Temuan penelitian mengindikasikan bahwa beragam simbol penyembuhan dalam naskah, seperti warna, hewan, benda pusaka, tanaman obat, dan mantra, tidak hanya berperan sebagai alat teknis dalam pengobatan, tetapi juga sebagai elemen spiritual yang memperkuat simbiosis antara manusia dan kekuatan supernatur. Simbol-simbol ini menunjukkan bahwa penyembuhan dalam tradisi Jawa bersifat holistik, menggabungkan dimensi fisik, mental, dan kosmologis.